Managing the relationship between natural spawning areas on unprotected floodplains and on protected man-made fishponds - Varga, Péter (Acta Agraria Debreceniensis, 2007)
The economic land management of unprotected floodplain areas is possible only if considered jointly with protected floodplain areas, for which facility fisheries provide a solution. One solution could be that a part of the natural fish increment of the spawning-grounds on unprotected floodplains be raised in protected side fishponds and then later sold. This kind of fishery utilization is also favourable from economic, conservationist and flood protection aspects.